Effects of Extractive Ammonia Pretreatment on the Ultrastructure and Glycan Composition of Corn Stover - Avci, Utku; Zhou, Xuelian; Pattathil, Sivakumar; da Costa Sousa, Leonardo; Hahn, Michael G.; Dale, Bruce; Xu, Yong; Balan, Venkatesh (Frontiers in Energy Research, 2019)
Lignocellulosic biomass is highly recalcitrant and requires a pretreatment step to improve the enzyme accessibility and fermentable sugar yields during enzymatic hydrolysis. Our previous studies demonstrated the rearrangement of the hydrogen bond network within CIII, makes it “amorphous-like” and facilitates easier glucan chain extraction by enzyme. Also, these changes increase the number of solvent-exposed glucan chain hydrogen bonds with water ~50% lowering the surface-bound cellulase by 60–70%. Also, major chemical modifications to lignin occur via ammonolysis of ester-linked ferulate and coumarate linkage. These apparent ultrastructural changes help the enhancement of cellulase activity resulting in higher production of fermentable sugars during enzyme hydrolysis of EA pretreated corn stover relative to Ammonia Fiber Expansion (AFEX) pretreatment. To understand ultra-structural modifications that occur during EA pretreatment, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) were used to examine untreated and EA-pretreated corn stover in an effort to visualize changes in the biomass resulting from the pretreatment. In addition, Immunofluorescence Microscopy was applied to both untreated and pretreated plant cell walls using glycan-directed monoclonal antibodies to reveal possible changes in the spatial distributions of wall glycan epitopes resulting from EA pretreatment. This evaluation was complemented with glycome profiling to determine the glycan epitope compositions of EA-pretreated cell walls relative to untreated and AFEX pretreated corn stover, where lignin and carbohydrates are not extracted. Distinct differences could be observed in the case of xyloglucan, unsubstituted and substituted pectin- and pectic-arabinogalactan-epitope levels in the plant cell wall after EA pretreatment compared with untreated and AFEX-pretreated walls. Liquid ammonia induced de-lignification of cell wall has helped to clearly identify the glucans that are intact after pretreatment. These studies support some of our hypothesis that liquid ammonia cleaves lignin–carbohydrate ester linkages, partially solubilizing lignin and its associated carbohydrates. Specifically, the imaging studies clearly show that some of the cell wall components are extracted as a separate liquid stream during the EA process, thereby creating porous, interconnected tunnel-like networks in the plant cell walls thereby providing better access of carbohydrate polymers to enzymes and thereby increasing the sugar yield from the EA-pretreated biomass.